A New Specimen of the Genus Octodontobradys (Orophodontidae, Octodontobradyinae) From the Late Miocene-Pliocene of the Southwestern Amazon Basin, Brazil - Guilherme, Edson; Bocquentin, Jean; Porto, Alice S. (Anuário do Instituto de Geociências, 2011)
This study presents an almost complete mandible of Octodontobradys sp. from the late Miocene-Pliocene of the Solimões Formation from a locality on the border between Brazil and Bolivia, in southwestern Amazonia. The two almost complete mandibular rami, together with fragments of fossils from other taxa, were found on the left bank of the Abunã River, upriver from the town of Plácido de Castro, in the Brazilian state of Acre. The form of the symphyseal region of the mandible, and the elongated and bilobated outline of the alveoli of the m2-3-4 molariforms place the specimen clearly in the genus Octodontobradys. However, the new specimen differs from O. puruensis in (a) the anterior position of the posterior external aperture of the mandibular canal, and (b) the wider and more anteriorly inclined symphyseal region. The mandible described here represents the first specimen of the genus Octodontobradys found outside of the holotype locality, Talismã, in the Brazilian state of Amazonas and enabled us to emend the diagnoses of Subfamily Octodontobradyinae.